‘A Mindful ACT’- testing the feasibility and acceptability of a brief psychosocial intervention designed to accompany osteopathy treatment for people who live with persistent pain - Julia Terry (International Journal of Osteopathic Medicine, 2021)
Background: Persistent pain represents a significant burden for individuals and society, exerting a profound effect on quality of life and posing a significant strain on healthcare resources. Novel interventions are needed to reduce the impact of psychological comorbidities on people who live with pain but also to improve pain self-management.ObjectivesThe aim of this research was to investigate the feasibility and acceptability of a brief group-based ACT intervention designed to osteopathy for people who live with persistent pain and psychological comorbidities.MethodsA mixed-method approach has been utilized that comprised of qualitative interviews providing an insight into peoples’ experiences of participating and quantitative data including psychological flexibility, depression, anxiety, fear avoidance and general health status. This preliminary report will only present the qualitative findings.ResultsA total of 9 participants took part in the intervention. The participants engaged well with the exercises and with the ACT model in general. Program attendance was high (4 out of the 9 participants attended all the 6 sessions, (further attendance is shown in the Supplementary file 7); all 9 took part in the post-intervention interview). Three major themes were identified from the interview data: Engaging with the ACT model, Experiences of taking part in the intervention and Perceived changes. The participants reported positive experiences: they found being able to connect with people who experience similar issues valuable and expressed that they liked the content and structure of the program. The intervention appeared to be feasible with the support of the osteopaths.ConclusionDelivering a brief ACT-based intervention for people living with persistent pain was found to be feasible and acceptable. The collaboration between osteopaths and psychologists in supporting people who live with persistent pain demonstrates potential and should be further explored in the future.